Investigation of band gap width in mixed ZnSxSe1–x crystals - Trubaieva, O. G.; Chaika, M. A. (Technology and design in electronic equipment, 2018)
Scintillators based on ZnSxSe1–x are promising materials for X-ray and γ-ray detection. For optoelectronic devices, it is better to use semiconductor compounds with a direct-zone energy structure with its spectral range lying in the fundamental absorption region. The band gap in such semiconductors is an important parameter that affects the energy resolution, ionization energy, dark current and other scintillation characteristics. The effect of sulfur content on the optical width of the band gap in mixed crystals ZnSxSe1–x is investigated in this paper. The test samples for this study were grown by Bridgman — Stockbarger in graphite crucibles with the diameter of 25 mm in the Ar atmosphere (PAr = 2·106 Pa) at a temperature from 1870 to 2000 K, depending on the composition of the initial raw materials. Six samples with different content of components were obtained: ZnS0,07Se0,93; ZnS0,15Se0,85; ZnS0,22Se0,78; ZnS0,28Se0,72; ZnS0,32Se0,68; ZnS0,39Se0,61. The transmittance of the samples in the range from 61 to 67% at 1100 nm (sample thickness 4 mm) indicates a high optical quality of the crystals. It was established that the optical width of the band gap for mixed crystals ZnSxSe1–x increases from 2.59 to 2.78 eV with increasing sulfur content from 0.07 to 0.39 for direct transitions and from 2.49 to 2.70 eV for indirect transitions. A comparison was made between theoretical and experimentally obtained values of the band gap width.It is shown that no new (defective) levels appear in the band gap. The smooth dependence of the optical band gap on the composition indicate a possibility of growing ZnSxSe1–x mixed crystals by directional solidification techniques for X-ray and γ-ray detectors. The wider band gap and higher atomic mass ratio of ZnSxSe1–x crystals, as compared to ZnSe(Te) or/and ZnSe(Al) crystals, extend application areas of such semiconductor material.